1998
DOI: 10.1021/jp981061a
|View full text |Cite
|
Sign up to set email alerts
|

Site Switching and Surface Restructuring Induced by NO Adsorption on Pt{110}

Abstract: We present the first infrared vibrational study of the adsorption of NO on Pt{110} over a wide range of temperatures. Adsorption is strongly dependent on both temperature and coverage, with many different species being formed on the surface. Under all conditions, site switching is observed during NO adsorption: at low coverages bridge-bonded species are formed on the surface, and at very high coverage NO switches to on-top sites. Other species, not previously reported, are also observed, depending on both adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 24 publications
5
53
0
Order By: Relevance
“…These results beautifully illustrate the reversible conversion between bridged NO(a) and linear NO(a) on Pt(1 1 0) driven by the coverage-dependent strong repulsive interactions. Similar phenomenon was previously observed for NO/Pt(1 1 0) by means of infrared vibrational spectroscopy: the bridgebonded species is stable at low coverages, but it converts into the atop species at high coverages [11,18].…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…These results beautifully illustrate the reversible conversion between bridged NO(a) and linear NO(a) on Pt(1 1 0) driven by the coverage-dependent strong repulsive interactions. Similar phenomenon was previously observed for NO/Pt(1 1 0) by means of infrared vibrational spectroscopy: the bridgebonded species is stable at low coverages, but it converts into the atop species at high coverages [11,18].…”
Section: Resultssupporting
confidence: 86%
“…Here we assigned the linear and bridged NO(a) species on Pt(1 1 0)-(1 · 2) simply on basis of the observed N-O vibrational frequencies. Similar site assignments on basis of the vibrational spectroscopy for NO have also been reported before [11,18]. However, vibrational features of adsorbed species, particularly of NO, are not sufficient to make the accurate adsorption site assignments, therefore, the nature of the adsorption sites of NO(a) Pt(1 1 0)-(1 · 2) on need to be verified by further structural measurements.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…An absorption band of around 1750 cm −1 could be due to NO molecules at on-top sites of the step. In the previous IRAS studies of NO on Pt(110) [32,33], a broad peak at 1758 cm −1 was observed at high coverage and the peak at 1626 cm −1 decreased coincidentally. The 1626 cm −1 peak originates from bridge NO species on the Pt row of Pt(110).…”
Section: Iras Measurements Of No Adsorption On Pt(997) At 140 Kmentioning
confidence: 76%